Β‐Hydroxyamide‐Based Ligands and Their Use in the Enantioselective Borane Reduction of Prochiral Ketones. Issue 1 (6th November 2013) - Azizoglu, Murat; Erdogan, Asli; Arslan, Nevin; Turgut, Yilmaz
ABSTRACT Hydroxyamide‐based ligands have occupied a considerable place in asymmetric synthesis. Here we report the synthesis of seven β‐hydroxyamide‐based ligands from the reaction of 2‐hydroxynicotinic acid with chiral amino alcohols and test their effect on the enantioselective reduction of aromatic prochiral ketones with borane in tetrahydofuran (THF). They produce the corresponding secondary alcohols with up to 76% enantiomeric excess (ee) and good to excellent yields (86‐99%). Chirality 26:21–26, 2013. © 2013 Wiley Periodicals, Inc.